2020
DOI: 10.1371/journal.pone.0227246
|View full text |Cite
|
Sign up to set email alerts
|

The association between dietary patterns before and in early pregnancy and the risk of gestational diabetes mellitus (GDM): Data from the Malaysian SECOST cohort

Abstract: Generally, dietary patterns (DP)s have been linked to the risk of diabetes mellitus, however, only few studies examined the associations between DPs in early pregnancy and the risk of gestational diabetes mellitus (GDM). This study aims to determine the association between DPs before and during pregnancy and risk of GDM in Malaysian pregnant women. DPs were derived using principal component analysis of consumed 126 food and beverage items assessed using a validated semi-quantitative food frequency questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 55 publications
(69 reference statements)
0
24
0
Order By: Relevance
“…Poor dietary habits are also a risk factor for GDM among Southeast Asian women [57]. A higher intake level of seafood protein [58,59] and less fiber [60] in daily meals has been reported to increase the risk of GDM during pregnancy.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Poor dietary habits are also a risk factor for GDM among Southeast Asian women [57]. A higher intake level of seafood protein [58,59] and less fiber [60] in daily meals has been reported to increase the risk of GDM during pregnancy.…”
Section: Risk Factorsmentioning
confidence: 99%
“…In contrast, a Mediterranean pattern and a healthy dietary pattern characterized with vegetables, rye bread, fruits and berries, and fish are associated with a decreased risk of GDM [18][19][20]. Again, some other investigators have not found any links between dietary patterns and the risk of GDM [21,22]. The most recent suggestion has been that the inflammatory potential of the diet may be associated with various diseases [23] including GDM [24].…”
Section: Introductionmentioning
confidence: 99%
“…A further stratified analysis of BMI at first prenatal visit and GWG at the second trimester revealed that particularly women with height < 150 cm, OW/OB and excessive GWG at the end of the second trimester were significantly at higher risk for developing GDM. The associations between higher pre-pregnancy BMI and excessive GWG with the risk of GDM have not only been established in previous studies [ 35 , 36 ] but also in previously reported data of a prospective cohort study in Malaysia (SECOST) [ 30 , 37 , 38 ]. It is possible that women with short stature and higher pre-pregnancy BMI have limited muscle and higher fat mass [ 39 ].…”
Section: Discussionmentioning
confidence: 81%